PENINGKATAN KEMAMPUAN MENYIMAK DONGENG DENGAN METODE MIND MAP MELALUI MEDIA ANIMASI AUDIO VISUAL DALAM MATA KULIAH MENYIMAK KARYA SASTRA DI IKIP BUDI UTOMO MALANG - Luly Zahrotul Lutfiyah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2018)
This research aims to (1) describe the implementation of mind map method through audiovisual animation media in improving listening to fairy tale ability, (2) describe the achievement level of mindmap method through audiovisual animation media in defining interesting parts from the fairy tale including (figure, character, and theme), (3) describe achievement level of mind map method through audiovisual animation media in showing interesting parts about the relevance between theme and recent situation, (4) describe achievement level of mind map method through audiovisual animation media in defining interesting parts of a fairy tale using logical reason, (5) describe achievement level of mind map method through audiovisual animation media in improving the ability to conclude the message of a fairy tale. This is a classroom action research (CAR). The data collection applies five techniques such as (1) Observation, (2) Interview, (3) Test, (4) Documentation, dan (5) Field Note. Mind map teaching methodthrough audiovisual animation media can improve ability in listening to fairy tale for the IKIP BUDI UTOMO Students. Based on evaluation result from cycle 1 and cycle 2, it is confirmed that the cumulative score improves; also, each aspect experiences the same improvement – except in the attractiveness of fairy tale relevance. Content comprehension aspect at cycle 1 gets score in percentage of 82% and at cycle 2 makes 90%. Fairy tale attracting parts aspect at cycle 1 reaches score in percentage of 34% and becomes 51% at cycle 2; fairy tale relevance attractiveness aspect at cycle 1 has score in percentage of 62%, and 54% at cycle 2; the aspect of expressing fairy tale interesting parts in logical reason at cycle 1 makes percentage score as many as 74% and becomes 87% at cycle 2, fairy tale conclusion message aspect at cycle 1 makes score of 75%, and 79% at cycle 2; furthermore, the student cumulative score in cycle 1 is 72% and becomes 80% at cycle 2. From the observation result, there also occurs improvement, and generally the teaching and learning atmosphere is quite conducive. The class situation is controllable, students feel favorable to mind map method and fairy tale VCD which are used as the media to listen to the fairy tale. Student interest in following fairy tale listening activity is relatively high. Things to suggest for further research, suppose it explores the implementation of mind map teaching method in the effort of improving student’s affective aspect. For Bahasa Indonesia teacher, suppose he/she applies mind map teaching method through audiovisual animation media as a kind of variation in teaching method tomake student not bored while joining the learning.